Whey protein supplementation does not accelerate recovery from a single bout of eccentric exercise - Hilkens, L.; De Bock, J.; Kretzers, J.; Kardinaal, A. F. M.; Floris-Vollenbroek, E. G.; Scholtens, P. A. M. J.; Horstman, A. M. H.; van Loon, L. J. C.; van Dijk, J.-W. (Journal of Sports Sciences, 2021)
The current double blind, randomized, placebo-controlled trial with two parallel groups aimed to assess the impact of whey protein supplementation on recovery of muscle function and muscle soreness following eccentric exercise. During a 9-day period, forty recreationally active males received twice daily supplementation with either whey protein (PRO; 60 g/day) or an iso-energetic amount of carbohydrate (CON). Muscle function and soreness were assessed before, and 0, 3, 24, 48, and 72 h after performing 100 drop jumps. Recovery of isometric maximal voluntary contraction (MVC) did not significantly differ between groups (timextreatment, P = 0.56). In contrast, the recovery of isokinetic MVC at 90°·s-1 was faster in CON as opposed to PRO (timextreatment interaction, P = 0.044). Recovery of isokinetic MVC at 180°·s-1 was also faster in CON as opposed to PRO (timextreatment interaction, P = 0.011). Recovery of countermovement jump performance did not differ between groups (timextreatment interaction, P = 0.52). Muscle soreness, CK and CRP showed a transient increase over time (P < 0.001), with no differences between groups. In conclusion, whey protein supplementation does not accelerate recovery of muscle function or attenuate muscle soreness and inflammation during 3 days of recovery from a single bout of eccentric exercise.